1972
DOI: 10.1172/jci107128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rheumatoid Factor on Complement-Mediated Phagocytosis

Abstract: Foundation, Rochester Minnesota 55901 A B S T R A C T The frequency and amount of IgM rheumatoid factor (RF) in the blood of patients with rheumatoid arthritis (RA) correlate with the severity of the disease and the number of complications. Though previous studies of RF in subacute bacterial endocarditis have shown that RF inhibits phagocytosis of microorganisms by granulocytes, the presence of low levels of complement (C) in blood and synovial fluid of patients with the highest titers of RF suggests that an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1974
1974
1981
1981

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…The demonstration that uptake of the early complement component, C4, correlates directly with percent hemolysis and that hemolysis is inhibited by EGTA (49) and antisera to early com- (11,12), GPC is as effective as HuC in lysing the SRC sensitized with RF. Our findings are in agreement with the recent demonstration of complement fixation by RF reported by Tesar and Schmid (15) and contrast with the report of McDuffie and Brumfield (21).…”
Section: Discussionsupporting
confidence: 91%
“…The demonstration that uptake of the early complement component, C4, correlates directly with percent hemolysis and that hemolysis is inhibited by EGTA (49) and antisera to early com- (11,12), GPC is as effective as HuC in lysing the SRC sensitized with RF. Our findings are in agreement with the recent demonstration of complement fixation by RF reported by Tesar and Schmid (15) and contrast with the report of McDuffie and Brumfield (21).…”
Section: Discussionsupporting
confidence: 91%
“…The inhibition of EAIgG binding and phagocytosis by RA sera may represent an effect of rheumatoid factor, perhaps a hidden rheumatoid factor, in our apparently rheumatoid factor-negative sera. McDuffie and Brumfield demonstrated that addition of rheumatoid factor to sheep red blood cells coated with IgG antibody inhibited phagocytosis of these cells by neutrophils (35). Lamers suggested that IgM rheumatoid factor may decrease processing of DNA-anti DNA complexes by binding with the Fc part of the complex and hence decreasing available Fc terminals to bind to the phagocyte Fc receptor (36).…”
Section: Discussionmentioning
confidence: 99%
“…Patient population 41 consecutive patients whose diagnostic renal biopsies were submitted for histological examination were studied. Clinical records were reviewed to evaluate current and past levels of renal function and to search for clues to the etiology of the renal disease.…”
Section: Methodsmentioning
confidence: 99%
“…Most likely this would occur in circumstances where the antiglobulins increased the size of immune complexes above that which readily deposit in glomerular capillaries. In vitro evidence can also be cited to suggest that, under certain conditions, antiglobulins can inhibit complement-mediated tissue injury (40,41). On the other hand, McCormick, Day, Morris, and Hill have presented data which suggest that antiglobulin-rich serum fractions can augment the tissue injury caused by nephrotoxic antisera (16).…”
Section: Serologic Techniquesmentioning
confidence: 99%